PENGARUH FAKTOR FRAUD HEXAGON THEORY TERHADAP KECURANGAN LAPORAN KEUANGAN - Chintia Nabiilah (2022)
This study is a quantitative study that aims to determine the effect of the fraud hexagon theory factors on financial statement fraud in consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The purposive sampling method was used by researchers to determine the research sample and consisted of 69 observations from 23 companies that matched the sample selection criteria. Multiple linear regression analysis with the help of STATA v.14 application was used to test the hypothesis. The results of the study state that (1) external pressures have a negative effect on financial statement fraud, (2) the nature of the industry has a negative effect on financial statement fraud, (3) auditor turnover has no effect on financial statement fraud, (4) director turnover does not. has an influence on financial statement fraud, (5) ceo duality has no effect on financial statement fraud, (6) political connections have no influence on financial statement fraud.